PENGARUH LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI PADA KANTOR DINAS KELAUTAN DAN PERIKANAN PROVINSI SULAWESI TENGAH - SIDIK, MOHAMMAD RHAMADHANI (Fakultas Ekonomi Universitas Tadulako, 2016)
This study aims to determine the influence of Physical Work Environment and Non Physical Work Environment Against Job Satisfaction of Employees Office of Marine and Fisheries Office of Central Sulawesi Province. Independent variable of this research is Physical Work Environment (X1) and Non Physical Work Environment (X2). While the dependent variable is Job Satisfaction (Y). The research method is quantitative descriptive method. The type of data used in this study is quantitative data while the data sources used are primary and secondary data. The population used in this study were 216 respondents. The sample of this research is 68 respondents with sampling technique that is proportional random sampling. Data analysis method used in this research is multiple linear regression analysis method. The results of this study indicate that the physical work environment and non physical work environment simultaneously affect the variable Job satisfaction. Partially the working environment of physical and non working physical environment have an effect on to job satisfaction of officer at office of Marine and Fishery Office of Central Sulawesi Province